Pergeseran Sentral Geopolitik Internasional, dari Heartland ke Asia Pasifik, Apa Geopolitic Leverage Indonesia ? - Zulkarnain Zulkarnain; Hendra Maujana Saragih; Safrizal Rambe; Hendrajit - Hendrajit (Populis : Jurnal Sosial dan Humaniora, 2018)
Indonesia has strategic geopolitics in global interaction, besides its position between two oceans and two continents which is an opportunity for how big a role that can be played on the international stage, also has a variety of natural resources. But this nation is not able to "manage" appropriately and well the location of the "strategic" position and wealth of natural resources that it has. Maybe only in the Bung Karno era, Indonesia was able to manage its geopolitics Key words: Geopolitics, Geopolitical Constellation, Indonesian Geopolitics, Threats